Nanomedicine in Oncocardiology: Contribution and Perspectives of Preclinical Studies - Borges, Gabriel Silva Marques; Lages, Eduardo Burgarelli; Sicard, Pierre; Ferreira, Lucas Antônio Miranda; Richard, Sylvain (Frontiers in Cardiovascular Medicine, 2021)
Cancer and cardiovascular diseases are the leading causes of death and morbidity worldwide. Strikingly, cardiovascular disorders are more common and more severe in cancer patients than in the general population, increasing incidence rates. In this context, it is vital to consider the anticancer efficacy of a treatment and the devastating heart complications it could potentially cause. Oncocardiology has emerged as a promising medical and scientific field addressing these aspects from different angles. Interestingly, nanomedicine appears to have great promise in reducing the cardiotoxicity of anticancer drugs, maintaining or even enhancing their efficacy. Several studies have shown the benefits of nanocarriers, although with some flaws when considering the concept of oncocardiology. Herein, we discuss how preclinical studies should be designed as closely as possible to clinical protocols, considering various parameters intrinsic to the animal models used and the experimental protocols. The sex and age of the animals, the size and location of the tumors, the doses of the nanoformulations administered, and the acute vs. the long-term effects of treatments are essential aspects. We also discuss the perspectives offered by non-invasive imaging techniques to simultaneously assess both the anticancer effects of treatment and its potential impact on the heart. The overall objective is to accelerate the development and validation of nanoformulations through high-quality preclinical studies reproducing the clinical conditions.